Место Лотмана в становлении нарратологии - Тюпа, Валерий Игоревич (SlavVaria, 2022)
The paper reconstructs the influence of the semiotic studies of Lotman on the formation of the prob-lems and the scientific apparatus of modern ("post-classical") multimedia nar-ratology, associated with the names of J. Genette, P. Ricoeur, W. Schmid and others. In particular, we discuss the emergence of scientific interest in the film narrative, which has also had a significant impact on literary narratology, enriching it with the constructive concept of the "narrative image". The article focuses on Lotman's storytelling research, especially the concept of " plot texts" of culture in their opposition to "plotless texts". Particular importance is attached to the distinction between plot and myth, which continued O.M. Freidenberg's investigations into the origin of narration. Lotman's pioneering role in mastering the scientific categories of "narrative picture of the world" and "narrative event" is revealed. The author reveals the place of Lotman's scientific heritage in the comprehension of narrative practices as a tool for mental appropriation of life, accumulation and retranslation of event experience, as well as in the birth and development of the modern project of historical narratology.